ANALISIS PENGARUH UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP CORPORATE SOCIAl RESPONSIBILITY DISCLOSURE PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA DI BURSA EFEK INDONESIA PADA TAHUN 2013-2019 - Sintia Safrianti (Creative Research Management Journal, 2020)
The aim of the study is to know factors that influence Corporate Social Responsibility Disclosure in the Basic and Chemical Industry Sector. Variables investigated in this study were size of company and age of company. The method used in this study is tocollect data, and then it will be analyzed using quantitative analysis methods. The populations in this study were companies thatcarry out Social Responsibility Disclosure, 28 sample companies selected in this study used purposive sampling methodology. The data analysis method was multi linier regression with significance level of 5%. The result of the study showed that : (1) Company size has a significant effect on CSRD. This shows that large scale companies will do more disclosure of their social responsibility; (2) The age of the company is not significant for CSRD. This shows the length of the company does not affect the disclosure of social responsibility.